The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnmol.2021.654031
|View full text |Cite
|
Sign up to set email alerts
|

SOX Transcription Factors as Important Regulators of Neuronal and Glial Differentiation During Nervous System Development and Adult Neurogenesis

Abstract: The SOX proteins belong to the superfamily of transcription factors (TFs) that display properties of both classical TFs and architectural components of chromatin. Since the cloning of the Sox/SOX genes, remarkable progress has been made in illuminating their roles as key players in the regulation of multiple developmental and physiological processes. SOX TFs govern diverse cellular processes during development, such as maintaining the pluripotency of stem cells, cell proliferation, cell fate decisions/germ lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 266 publications
(460 reference statements)
2
70
0
Order By: Relevance
“…Sox proteins are architectural components of chromatin ( Pevny and Lovell-Badge, 1997 ), which govern neuronal and glial lineage specification during development. In the regenerating adult PNS, Sox members are pioneer TFs that poise downstream TFs for transcriptional regulation ( Stevanovic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sox proteins are architectural components of chromatin ( Pevny and Lovell-Badge, 1997 ), which govern neuronal and glial lineage specification during development. In the regenerating adult PNS, Sox members are pioneer TFs that poise downstream TFs for transcriptional regulation ( Stevanovic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further explore how these gene expression changes might have happened, we next performed transcription factor (TF) target enrichment analysis to identify potential upstream TFs responsible for observed changes in gene expression of Nutlin-3-treated Fmr1 KO mice. Our analysis showed that the top TFs are mainly involved in stem cell fate specification (such as MEOX1, MEOX2, PRRX1, BNC2, SOX18 and TWIST1) [47][48][49][50][51] and/or extra cellular matrix organization (such as HEYL,TBX18, PRRX1, PRRX2 and TCF21 ) [52][53][54] (Fig. 6a; ;Additional file 3: Fig.…”
Section: Transient Nutlin-3 Treatment Leads To Significant and Specif...mentioning
confidence: 94%
“…Disruption of the interactions of transcription factors with the transcription complex results in the downregulation of the selected gene. For example, SRY (sex determining region Y)-box 2, SOX2, is a transcription factor that plays an essential role in early embryonic development and neural differentiation [72]. SOX2 is co-expressed with SYN in the Lewy bodies in the brain of PD patients [73], where SYN is also co-localized with TPPP/p25 [27].…”
Section: Regulation At Gene Level: Transcription Factorsmentioning
confidence: 99%